Laws of differentiation of an environment of Caucasus as a basis for the bioecological analysis - A. M. Bakhtiev (Юг России: экология, развитие)
In this publication the system of changes in nature and in climate of the Caucasus from the northwest to south-east direction are researched as a basis for the analysis of the condition of the animals and plants.